#TITLE_ALTERNATIVE# - NUNI WAHYUNI (NIM : 20912002); Pembimbing : Dr. Agus Yodi Gunawan, INTAN
Condensate is a liquid condensed from gas that is formed due to the lowering of pressure at the base of the gas well. In this thesis, the dynamics of the condensate motion in a vertical gas well is modeled mechanistically. The model is constructed by involving forces such as gravity, the drag force, and the buoyancy force due to condensate environment. The buoyancy force affects the condensate to move up- ward or downward depending on the initial height of condensate. The model is simulated in two dimensions, for several values of gas velocity. Results shows that the greater the gas velocity, the more condensate move to the surface of the gas well.